Effects of acupuncture combined with five-element music for people with mild/moderate post-stroke depression: A randomized controlled trial - Jinglong Sun; Xia Zhou; Binbin Ren; Youhua Guo; Qifeng Xu; Qin Wang; Ziyun Feng; Qingqing Jia; Wenwen Li; Li Li; Shouqiang Chen (Elsevier, 2024)
Objectives: To evaluate the efficacy and safety of acupuncture combined with five-element music (FEM) as an therapeutic strategy for the physical and mental state of Post-stroke depression patients. Design and setting: Multicenter, randomized clinical trial conducted at 3 hospitals in China and enrolling 237 patients with PSD between June 2019 and April 2021. Participants mild/moderate PSD (17-item GRID Hamilton Depression Scale (HAMD) score 7-24) were randomly assigned (1:1) to acupuncture combined with FEM (AFEM) group or cognitive behavioral therapy (CBT) group. Main outcome measures: The primary outcome was change and differences between the groups in HAMD-17 from baseline to week 12. Secondary outcomes included Fugl-Meyer Assessment Scale score and Stroke-Specific Quality of Life Scale (SS-QOL) score. Results: The 237 patients in this intention-to-treat analysis were randomized into either the AFEM group (n=119) or the cognitive behavioral therapy (CBT) group (n=118). Of these 237 participants, 225 (94.9 %) completed all outcome measurements at week 12. The AFEM and CBT groups both showed significant improvement in HAMD-17 from baseline to week 12. Patients in the AFEM group had significantly lower HAMD-17 scores of −3.56 at week 8 (95 % CI,-4.59 to −2.53; p <.001) and −3.50 at week 12 (95 % CI,-4.53 to −2.46; p<.001) than patients in the CBT group. The SS-QOL score improved significantly at week 12. The Fugl-Meyer score was significantly lower in the AFEM group than in the CBT group at week 4, but this difference was not statistically significant upon follow-up at weeks 8 and 12. The incidence of treatment-related adverse events was 2.1 % in the AFEM group, with no serious adverse events reported. Conclusions: The results suggest that acupuncture and five-element music significantly improve the depressive symptoms in this cohort of Chinese PSD patients, and the toxicities were similar with CBP group. Registration: This study registered with the ClinicalTrials.gov Identifier: ChiCTR1900023741.